2006
DOI: 10.1128/jvi.80.7.3582-3591.2006
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Local Symmetry Interactions Globally Stabilize a Mutant Virus Capsid That Maintains Infectivity and Capsid Dynamics

Abstract: Structural transitions in viral capsids play a critical role in the virus life cycle, including assembly, disassembly, and release of the packaged nucleic acid. Cowpea chlorotic mottle virus (CCMV) undergoes a well-studied reversible structural expansion in vitro in which the capsid expands by 10%. The swollen form of the particle can be completely disassembled by increasing the salt concentration to 1 M. Remarkably, a single-residue mutant of the CCMV N-terminal arm, K42R, is not susceptible to dissociation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
87
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 65 publications
(96 citation statements)
references
References 54 publications
9
87
0
Order By: Relevance
“…2B). SDS-PAGE of the BMV CP treated with the same conditions revealed that less than 20% of the CP migrated to the position expected of the cleaved product and that the RNA was not fragmented (21) (Fig. 2C and 1B).…”
Section: Resultsmentioning
confidence: 99%
“…2B). SDS-PAGE of the BMV CP treated with the same conditions revealed that less than 20% of the CP migrated to the position expected of the cleaved product and that the RNA was not fragmented (21) (Fig. 2C and 1B).…”
Section: Resultsmentioning
confidence: 99%
“…Many other viruses have capsid proteins with positively charged and highly flexible sequences that translocate from within the virion to the external surface of the virion (7,53). It is possible that these sequences are acted on by host proteins to regulate the disassembly of the virions and enable viral gene expression and replication.…”
Section: Discussionmentioning
confidence: 99%
“…This large-scale motion is expected to be rare compared to the smaller transitions required for amide proton exchange in HDX. Protein dynamics on the nanometer scale are known to be involved in complex formation (53), viral capsid breathing (49,(54)(55)(56) and viral docking and entry events (57).…”
Section: Introductionmentioning
confidence: 99%